Measures of Displaced Commercial Risk on financial stability in Islamic banking institutions - Che Arshada, Noraziah; Zakaria, Roza Hazli; Sulaiman @ Mohamad, Ahmad Azam (Online Journal of Research in Islamic Studies, 2015)
Islamic banks are exposed to a unique risk such as Displaced Commercial Risk (DCR). DCR arises from the assets managed on behalf of the investment account holders which may be borne by the Islamic bank’s own capital, when the Islamic banks forgo part or all of its share of profits on the investment account holders funds, in order to increase the return to the investment account holders. In a dual banking system, DCR could be a threat to the Islamic banks given the competition of fixed and higher return from the conventional banks. However, DCR would not be a threat to Islamic banks if their account holders choose Islamic banks due to religious obligatory factor. This paper aims to examine whether DCR is a threat to Islamic banks’ stability. For that purpose, a model is set up to estimate bank stability. The model includes other bank specific characteristics and macroeconomic variables as control variables to avoid omitted variables bias. We find that DCR is one of the factor that affects bank profitability, at least in the case of Malaysian Islamic banks. This empirical evidence implies that Islamic banks operating in a dual banking system are affected by displaced commercial risk. Hence, it should be one of the banks’ risk management concern.